2023
DOI: 10.3855/jidc.17032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacist-initiated assessment and amelioration of appropriate antibiotic use in surgical units at a South Indian tertiary care hospital - A handshake approach

Abstract: Introduction: Studies on the appropriateness of antibiotic use among surgical patients are limited in developing countries, notably in India. Therefore, we aimed to evaluate the inappropriateness of antibiotic use, demonstrate the impact of clinical pharmacist interventions and determine the predictors of inappropriate use of antibiotics in the surgical units of a South Indian tertiary care hospital. Methods: This was a 1-year prospective interventional study on in-patients of the surgical wards to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The most common cause of inappropriate cases was overuse of antibiotics with a rate of 35.29%. It was observed that inappropriate prescriptions were mostly in cases involving the gastrointestinal system (28%) [ 15 ]. In our study, the lowest rate of appropriateness of cefazolin selection according to ASHP guidelines was thyroid and/or parathyroid surgery, with 13.6%, followed by breast surgery, with 89.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of inappropriate cases was overuse of antibiotics with a rate of 35.29%. It was observed that inappropriate prescriptions were mostly in cases involving the gastrointestinal system (28%) [ 15 ]. In our study, the lowest rate of appropriateness of cefazolin selection according to ASHP guidelines was thyroid and/or parathyroid surgery, with 13.6%, followed by breast surgery, with 89.9%.…”
Section: Discussionmentioning
confidence: 99%